THE EFFICIENCY AND PRODUCTIVITY OF THEREGIONAL DEVELOPMENT BANKS IN INDONESIA: AN APPLICATION OF DATA ENVELOPMENT ANYLYSIS (DEA)- MULTISTAGE (INPUT ORIENTED VRS) APPROACH COMPARE WITH CAMEL APPROACH - Sengkey, Marthen (JBE (Journal of Business and Economics); Volume 6 No.1, 2007 JBE UNKLAB, 2007)
The study employs DEA-Multistage (input oriented VRS)-model to investigate the efficiency and productivity of the 26 regional development bank in Indonesia from 1994 to 2004. DEA results suggest that the average estimate scores of sample banks have ranged from 19.14 percent to 69.14 percent. From this approach, BPDWS is the most efficient with the highest average estimate efficiency score of 69.14 percent and has the lowest average input inefficiency of 30.86 percent. On the other hand BPDP has the lowest average efficiency score, whis is 19.14 percent with the highest average input inefficiency of 80.86 percent. Moreover, 69.2 percent of banks have the estimate efficiency score above the mean of 33.28 percent. In general, the efficiency scores of all banks showed a decline when the financial crisis stuck the Asian region in 1997. Another significant contribution of DEA model is a possible explicit determination of bank’s excesses in input resources and also output deterioration for the first itme in Indonesia development banks. Among four input variables, capitas has the highest average input slack of 11.26 percent followed by deposit, fixed assets and total operating expenses with the average imput slacks of 10.13 percent, 6.44 percent, 6.44 percent, and 3.65 percent respectively.